Antibacterial Activity of Synthetic Cationic Iron Porphyrins - Artak Tovmasyan; Ines Batinic-Haberle; Ludmil Benov (MDPI AG, 2020)
Widespread antibiotic resistance demands new strategies for fighting infections. Porphyrin-based compounds were long ago introduced as photosensitizers for photodynamic therapy, but light-independent antimicrobial activity of such compounds has not been systematically explored. The results of this study demonstrate that synthetic cationic amphiphilic iron N-alkylpyridylporphyrins exert strong bactericidal action at concentrations as low as 5 μM. Iron porphyrin, FeTnHex-2-PyP, which is well tolerated by laboratory animals, efficiently killed Gram-negative and Gram-positive microorganisms. Its bactericidal activity was oxygen-independent and was controlled by the lipophilicity and accumulation of the compound in bacterial cells. Such behavior is in contrast with the anionic gallium protoporphyrin IX, whose efficacy depends on cellular heme uptake systems. Under aerobic conditions, however, the activity of FeTnHex-2-PyP was limited by its destruction due to redox-cycling. Neither iron released from the Fe-porphyrin nor other decomposition products were the cause of the bactericidal activity. FeTnHex-2-PyP was as efficient against antibiotic-sensitive E. coli and S. aureus as against their antibiotic-resistant counterparts. Our data demonstrate that development of amphiphilic, positively charged metalloporphyrins might be a promising approach in the introduction of new weapons against antibiotic-resistant strains.